Bilateral High Intra‐Abdominal Testes Successfully Treated With Multistage Fowler–Stephens Orchiopexy to Preserve Testicular Function - Akari Hiraguri; Yuichi Sato; Junya Hata; Yusuke Kirihana; Akihisa Hasegawa; Satoru Meguro; Kanako Matsuoka; Seiji Hoshi; Souichiro Ogawa; Yoshiyuki Kojima (IJU Case Reports)
ABSTRACT Introduction A case of bilateral high intra‐abdominal testes successfully treated with multistage Fowler–Stephens orchiopexy is reported. Case Presentation A 6‐month‐old boy with bilateral nonpalpable testes was diagnosed with a left intra‐abdominal testis located immediately caudal to the spleen on magnetic resonance imaging and laparoscopy. At the age of 4 years, diffusion‐weighted magnetic resonance imaging detected a structure immediately caudal to the liver, which was suspected to be the right testis. With a diagnosis of bilateral intra‐abdominal testes, one‐stage Fowler–Stephens orchiopexy was performed on the right testis at 5 years of age. After confirming its development, two‐stage Fowler–Stephens orchiopexy was performed on the left testis at 10 years of age. Conclusion After confirming the development of the right testis that underwent one‐stage Fowler–Stephens orchiopexy, two‐stage Fowler–Stephens orchiopexy was completed on the left testis, resulting in the successful preservation of both testes and normal sexual development.